2021
DOI: 10.1021/acsinfecdis.1c00392
|View full text |Cite
|
Sign up to set email alerts
|

Poly(l-ornithine)-Grafted Zinc Phthalocyanines as Dual-Functional Antimicrobial Agents with Intrinsic Membrane Damage and Photothermal Ablation Capacity

Abstract: Multifunctional antimicrobial peptides that combine the intrinsic microbicidal property of cationic polypeptide chains and additional antibacterial strategy hold promising applications for the treatment of infections caused by antibiotic-resistant bacteria, especially "superbugs". In the present study, star-shaped copolymers ZnPc-g-PLO with a zinc phthalocyanine (ZnPc) core and four poly(L-ornithine) (PLO) arms were designed, synthesized, and evaluated as dualfunctional antimicrobial agents, that is, intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…The high cationic charge density of ZnPc-g-PLO micelles endowed them with potent and broad-spectrum antibacterial activities by physically disrupting bacterial membranes in the absence of laser irradiation, and the aggregation-induced high photothermal conversion efficiency of the ZnPc core resulted in a significant enhancement in bactericidal potency through effective photothermal sterilization. [22] Lee and his colleagues found that boronic acid-functionalized zinc(II) phthalocyanine (PcN4-BA) can serve as a novel PS for aPDT. The aggregation generally results in a substantial reduction in the generation of ROS derived from Pcs, exerting an adverse impact on photodynamic therapy.…”
Section: Self-assembled Nanoparticles Of Pcsmentioning
confidence: 99%
See 3 more Smart Citations
“…The high cationic charge density of ZnPc-g-PLO micelles endowed them with potent and broad-spectrum antibacterial activities by physically disrupting bacterial membranes in the absence of laser irradiation, and the aggregation-induced high photothermal conversion efficiency of the ZnPc core resulted in a significant enhancement in bactericidal potency through effective photothermal sterilization. [22] Lee and his colleagues found that boronic acid-functionalized zinc(II) phthalocyanine (PcN4-BA) can serve as a novel PS for aPDT. The aggregation generally results in a substantial reduction in the generation of ROS derived from Pcs, exerting an adverse impact on photodynamic therapy.…”
Section: Self-assembled Nanoparticles Of Pcsmentioning
confidence: 99%
“…[27] Magadla et al synthesized a range of ZnPcs with varying cation numbers (Figure 3a) and encapsulated them within SiNPs to prevent or reduce ZnPcs' aggregation and The preparation of ZnPc-g-PLO micelles and their mechanism of antibacterial activity. [22] Copyright (2021), with permission from American Chemical Society. (b) The schematic illustration of the nanostructured self-assembly of PcN4-BA.…”
Section: Pcs Combined With Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Multifunctional antimicrobial peptides that combine the intrinsic microbicidal property of cationic polypeptide chains and additional antibacterial strategy hold promising applications for the treatment of infections caused by antibiotic-resistant bacteria, especially “superbugs”. Zheng et al [ 83 ] designed and synthesized a star-shaped copolymer ZnPc-g-PLO with a zinc phthalocyanine (ZnPc) core and four poly(l-ornithine) (PLO) arms as a bifunctional antibacterial agent, i.e., intrinsic membrane damage and photothermal ablation capability. In an aqueous solution, amphiphilic ZnPc-g-PLO molecules self-assemble into nanosized polymeric micelles with an aggregated ZnPc core and star-shaped PLO periphery, where the ZnPc core exhibits appreciable aggregation-induced photothermal conversion efficiency.…”
Section: Antimicrobial Nanomedicine Drug Delivery Systemsmentioning
confidence: 99%